2001
DOI: 10.1063/1.1372365
|View full text |Cite
|
Sign up to set email alerts
|

Meyer–Neldel rule for dark current in charge-coupled devices

Abstract: Articles you may be interested inReduction of ultraviolet-radiation damage in SiO 2 using pulse-time-modulated plasma and its application to charge coupled 44 device image sensor processesWe present the results of a systematic study of the dark current in each pixel of a charged-coupled device chip. It was found that the Arrhenius plot, at temperatures between 222 and 291 K, deviated from a linear behavior in the form of continuous bending. However, as a first approximation, the dark current, D, can be express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Unfortunately the paper does not present data for other barrier energies, so it is not possible to find the Tmn associated with the transversal conduction he obtained. Widenhorn et al [29] calculated the MNR for the dark current in a silicon CCD and found a MN energy of 25meV, which is very close to our result.…”
Section: Iv-discussionsupporting
confidence: 81%
“…Unfortunately the paper does not present data for other barrier energies, so it is not possible to find the Tmn associated with the transversal conduction he obtained. Widenhorn et al [29] calculated the MNR for the dark current in a silicon CCD and found a MN energy of 25meV, which is very close to our result.…”
Section: Iv-discussionsupporting
confidence: 81%
“…Other important characteristics of dark current, such as the temperature dependence 14,15 and random telegraph behavior 16,17 , are also begging for better characterization and simulation models. This presents a fruitful avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…13 Widenhorn et al calculated the MN rule for the dark current in a silicon CCD and found an energy value of 25.3 meV. 14 The same authors reported an energy value of 56.5 meV for forward current in diodes. 15 Coutts and Pearsall found 31 meV for the reverse current of solar cells.…”
Section: -2mentioning
confidence: 99%